Features of Development of the System of Secondary Schools Educational Establishments on Liberated from German Occupation Territory of the Ukrainian SSR: to the Question about the Sources of Research - Natalya Antonets (Pedagogical Discourse, 2013)
In the article materials which were published in the restored in May 1944 the newspaper «Soviet education» are examined, as sources base, for research of features of development of the system of general educational institution on liberated from German occupation territory of Ukrainian SSR in the period of continuation of military operations on fronts of Second world war. In particular, attention is spared to adjusting of activity of primary, middle and secondary schools, childʼs houses, special schools, and also to network of schools of working and rural young people, introduction in the cities of separate studies of boys and girls and creation in this connection of masculine and womanish educational institution.